A model of advective changes in air humidity: a stochastic approach. (10th November 2020) - Nozhkin, Vladimir S.; Zadorozhniy, Vladimir G.; Ulshin, Igor I.; Kanishcheva, Olesya I.
The paper presents a novel approach to the solution of a moisture transfer problem described by a differential equation with the coefficients which are treated as random processes. The distribution of the projections of the instantaneous velocity vector is approximated by the Vaga-Ising law, and the parameters of such distribution are identified based on a bionic model of adaptive search behaviour. Explicit expressions for the expectation and the second-moment function are obtained.